An online survey on clinical characteristics of otologic symptoms linked to COVID-19 infection - Wu, Linsui; Peng, Hongyi; He, Yufeng; Pu, Ling; Zhong, Shixun (Frontiers in Public Health, 2023)
Objective To report the otologic symptoms that present in patients with COVID-19 infection and investigate the pathogenic characteristics during the period of the pandemic. Materials and methods This cross-sectional descriptive study included participants with COVID-19 infection. COVID-19 infection was verified in these patients by nucleic acid test or antigen test. An online questionnaire was developed to analyze the association between the COVID-19 pandemic and the characteristics of otologic symptoms. Results This study included 2,247 participants, of which nearly half had one or more otologic symptoms. The presents of otologic symptoms were associated with gender (OR = 1.575, p < 0.0001), age (OR = 0.972, p < 0.0001), and occupation (healthcare worker: p < 0.0001; personnel of enterprises or institutions: OR = 1.792, p < 0.0001; student: OR = 0.712, p < 0.044). The otologic symptoms following COVID-19 infection in order were vertigo (25.95%), tinnitus (19.05%), otalgia (19.00%), aural fullness (17.18%), hearing loss (11.62%), otorrhea (1.25%), and facial paralysis (0.27%). Conclusion The present study shows that otologic symptoms are common among the COVID-19 infected participants and that these symptoms mostly recover spontaneously. During the corona-virus pandemic, the involvement of the cochleovestibular system and facial nerve should not be overlooked while treating the COVID-19 infected individuals.